PENGAMATAN PROSES SOSIALISASI MASYARAKAT TENTANG KERUKUNAN ANTAR UMMAT BERAGAMA DI DESA PASAR TIGA KEC. PANAI TENGAH KAB. LABUHANBATU - Alwi Ramadhan Harahap; Siti Mutiah Siregar; Afifah Azmi; Anwarsyah Nur (STIT AL-AMIN KREO TANGERANG, 2021)
The background of writing this article is the social life of the community. Where society is an interdependent community (mutually dependent on one another). In general, the term community is used to refer to a group of people who live together in an organized community, and socialization is a process of inculcating or transferring habits or values and rules from one generation to another in a group or society. A number of sociologists refer to socialization as a theory of roles (role theory). Because in the process of socialization, it is taught the roles that must be carried out by individuals, so that social solidarity is formed, and Harmony between religious communities is a way or means to bring together, regulate external relations between people who are not of the same religion or between religious groups in social life.